PARADIGMS REPRESENTING CHARACTER QUANTITY CHANGES AT THE PHONOLOGICAL/PHONETIC LEVEL IN ENGLISH AND UZBEK LANGUAGES (American Journal of Research in Humanities and Social Sciences, 2024)
This article devoted to the study paradigms representing character quantity changes at the phonological/phonetic level in English and Uzbek languages. As recognized in theoretical linguistics, language units have basically three types of relationships, i.e. syntagmatic, paradigmatic and hierarchical relationships. The important features (signs) of linguistic units are first determined on the basis of each level system, and then on the basis of the systems located below and above this level. if we take into account the theory of language-speech opposition of modern linguistics, we should call the level where sound types exist not "phonetic level", but "phonological level", to support such a view in linguistics.